กระแสธารความคิด “ไตรภูมิ” ในวรรณกรรมและภาพยนตร์ไทย (CONCEPTUAL CURRENTS OF “TRI BHUME” (THREE WORLDS) IN THAI LITERATURARY WORKS AND MOVIES) - Chomchoei, Karnrawee (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2012)
บทความนี้เป็นการศึกษากระแสธารความคิด “ไตรภูมิ” ที่ปรากฏในงานศิลปะไทยประเภทวรรณกรรมและภาพยนตร์ โดยเริ่มพิจารณาที่ไตรภูมิกถา วรรณคดีสมัยสุโขทัย ซึ่งเป็นวรรณคดีที่ได้กระตุ้นให้แนวคิด“ไตรภูมิ” ฝังรากลึกอยู่ในสังคมไทย และส่งอิทธิพลต่อความคิดของศิลปินในสมัยต่อมา จากการศึกษาพบว่า แม้ดูเหมือนว่ากระแสธารความคิดดังกล่าวอาจถูกบดบังไปด้วยปัจจัยอันเนื่องมาจากวิถีชีวิตของผู้คนในยุคโลกาภิวัตน์ แต่ก็ยังไม่สูญสลายไปจากระบบคิดของคนในสังคมไทย หากแต่ยังได้รับการเน้นย้ำผ่านงานศิลปะที่สร้างขึ้นใหม่และงานศิลปะร่วมสมัยอย่างต่อเนื่อง ทั้งยังสามารถสื่อสาร สร้างความกระทบใจแก่ผู้รับสารได้เป็นอย่างดี กระตุ้นให้เกิดความคิดที่เชื่อมโยงกับหลักธรรมในพระพุทธศาสนา กระแสธารความคิด “ไตรภูมิ” ซึ่งเป็นการมองชีวิต โลก และจักรวาลแบบคนโบราณในกรอบคิดของพระพุทธศาสนานี้ จึงยังทรงคุณค่าและมีค่าควรแก่การศึกษาเรียนรู้ทุกยุคทุกสมัย คำสำคัญ: กระแสธารความคิด ไตรภูมิ ภาพยนตร์ไทย วรรณกรรมไทย This article is based on the study of the conceptual currents of “Tri Bhume” (Three Worlds) in Thai literaturary works and movies. The study started with an examination of Tri Bhumikatha, the literary text of the Sukothai period which reinforces the “Tri Bhume” concepts to take deeper roots in Thai society and have continually influenced Thai artists of later periods. Although these concepts seem to have been eclipsed by elements resulted from life in the globalization era, they have not altogether lost from Thai people’s system of thoughts. Indeed, they have continually been emphasized through innovative and contemporary arts. Furthermore, they can effectively communicate with the audience, move the receivers of the messages, and provoke them to relate such notions with Buddhist principles. Therefore the conceptual currents of “Tri Bhume,” which views life, the earth, and the universe according to traditional Buddhist frame of thoughts are still invaluable and worth careful investigation despite the passage of time. Keywords: conceptual currents, Thai Literary, Thai movies, Tri Bhume